A novel phosphate ionic liquid plays dual role in synthetic ester oil: From synthetic catalyst to anti-wear additive. (May 2016) - Zhu, Lili; Zhao, Qin; Wu, Xinhu; Zhao, Gaiqing; Wang, Xiaobo
Abstract: A novel neutral ionic liquid 1-tetradecyl-3-(2-ethylhexyl)imidazolium bis(2-ethylhexyl) phosphate was synthesized and evaluated as catalyst in the esterification of trimethylolpropane (TMP) with oleic acid (OA) and anti-wear additive (AW) in trimethylolpropane oleate (TMPTO) for the first time. Results showed that the IL exhibited catalytic activity with an oleic acid conversion increased by 14% and a selectivity of 55.9% to di-ester, 44.1% to tri-ester in the esterification reaction under the optimum reaction conditions. And unlike most ILs that have little or no solubility in the synthetic ester fluids, this IL is fully miscible in TMPTO after reaction. More importantly, the IL dissolved in TMPTO significantly improved friction reducing and anti-wear properties of the base oil. Highlights: A novel neutral ionic liquid was synthesized and evaluated as catalyst. The IL is fully miscible with lubricating oil after reaction, without any separation. IL can effectively improve the tribological properties of the base oil as friction-reducing and anti-wear additives.